2017
DOI: 10.3389/fenvs.2017.00026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbial and Heavy Metal Contaminants on Environmental/Ecological Health and Revitalization of Coastal Ecosystems in Delaware Bay

Abstract: The presence of heavy metals, excess nutrients, and microbial contaminants in aquatic systems of coastal Delaware has become a public concern as human population increases and land development continues. Delaware's coastal lagoons have been subjected to problems commonly shared by other coastal Mid-Atlantic states: turbidity, sedimentation, eutrophication, periodic hypoxic/anoxic conditions, toxic substances, and high bacterial levels. The cumulative impact of pollutants from run-off and point sources has degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The higher levels at point A4 may be due to the proximity of the site to some agricultural activities along the strip. The concentration of phosphates has been correlated with agricultural practices involving the use of agro-based fertilizers in other studies ( 51 , 52 ). The higher concentration could also be attributed to runoffs from polluted industrial sections of the town to the lakefront.…”
Section: Discussionmentioning
confidence: 92%
“…The higher levels at point A4 may be due to the proximity of the site to some agricultural activities along the strip. The concentration of phosphates has been correlated with agricultural practices involving the use of agro-based fertilizers in other studies ( 51 , 52 ). The higher concentration could also be attributed to runoffs from polluted industrial sections of the town to the lakefront.…”
Section: Discussionmentioning
confidence: 92%
“…Our result is aligned with the study conducted by Chase et al [40] that the salinity (ranging from 1 to 35 ppt) was negatively correlated with V. vulnificus levels in water and sediments in their study. Ozbay et al [46] also found during the controlled laboratory experiment that oysters under low salinity treatments consistently yielded the highest total aerobic bacteria and Vibrionaceae levels. eir study confirms that high aerobic bacteria and Vibrionaceae levels are primarily salinity dependent.…”
Section: Correlation Betweenmentioning
confidence: 89%
“…The toxicity in the environment depends to a large extent on environmental conditions, as these influence the valence of the metal ions and thus their bioavailability ( Suvarapu and Baek, 2017 ). There is a growing understanding of the anthropogenic impact of metal contamination on the microbial community of aquatic ecosystems ( Ozbay et al., 2017 ; Yao et al., 2017 ; Igiri et al., 2018 ; Gillard et al., 2019 ; Rajeev et al., 2021 ; Liu et al., 2021 ).…”
Section: Anthropogenic Marine Ecosystems Pollution: An Approach To Th...mentioning
confidence: 99%